Urgensi Kesehatan Ibu dan Anak di Masa Pandemi Covid-19 - Lia Salvia Syahmalluddin (Saree : Research in Gender Studies, 2021)
The COVID-19 pandemic has had a very wide impact both in terms of economy, social order, and health. In the health sector, the COVID-19 pandemic has made health services only focused on dealing with Covid 19 and the number of health workers who have been exposed, resulting in the closure of various access to health services. Restrictions on activities and public concerns in visiting health care facilities have resulted in the slow interaction of the community, especially mothers and newborns, to health workers and health service facilities. Maternal and child health services are very important, especially in 1000 HPK (First Day of Life), because it is a time when the brain develops rapidly. A mother's health is important. Even though it looks small, the impact of mother's health is so big on the surrounding environment, especially on the child. A healthy mother will raise healthy children as well. The effect can be from the time the child is in the womb until he grows up. In short, a healthy mother will start an intergenerational cycle of health. The health of mothers and babies must be an important concern during the Covid-19 pandemic. If the maternal mortality rate is high and the quality of the babies born is not good, it will become a problem in the future such as stunting. Of course, this will affect the demographic bonus. In the current pandemic, health services must continue to run for mothers and children. If the suboptimal service conditions continue, it will have a serious impact on maternal and child health by increasing mortality and morbidity rates. Therefore, greater efforts are needed to prevent this from happening. It takes synergy between the government, health workers, and the community to prevent these problems from happening.